Problematika Pelayanan Terpadu Kepemilikan Status Hukum Perkawinan Masyarakat Gorontalo - Harsono Pulu Rahman; Ahmad Faisal (Pascasarjana IAIN Sultan Amai Gorontalo, 2019)
This article aims to uncover the problem of integrated service ownership over the legal status of the Gorontalo marriage community. This research uses descriptive qualitative method with a juridical sociological approach. The results showed that there were managerial problems in the management of integrated marriage services programs ranging from invalid data collection, lack of socialization, lack of community response, there were still institutions that had not implemented bureaucratic pruning, to aspects of collective evaluation. The results of the study also recommend several things that need to be improved and become a solution, namely: cross-sectoral coordination that is strengthened by the formation of a joint committee, budgeting must be given since data collection, joint strengthening Standard Operating Procedures, relevant agencies must be given a legal umbrella to be able to cut the bureaucracy in the field, this program must be accompanied by other incentive programs aimed at minimizing the occurrence of unregistered marriages.